MINT occupations - claims of a skills shortage are often overstated : analyses from the first BIBB-IAB Qualification and Major Occupational Field Projection - Bott, Peter [Verfasser]; Helmrich, Robert [Verfasser]; Zika, Gerd [Verfasser] (My University, 2011)
"Analyses from the first BIBB-IAB Qualification and Major Occupational Field Projection MINT occupations, the umbrella term for job qualifications involving mathematics, information technology, natural sciences and technology, are often cited as a prime example of the imminent skills shortage. This apparent perception of a skills shortage is the subject of the following article. The principal question is whether there is actually any problem with the supply of newly qualified workers. With the help of reference data from official statistics on this occupational field and the first interpretations of the BIBB-IAB Qualification and Major Occupational Field Projections, the article aims to give a more nuanced description of the real situation in this occupational field." (Autorenreferat, BIBB-Doku)
Keywords: S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; S 6.3.2 Techniker, Technische Sonderkräfte, Zeichner, Industriemeister (ausgenommen IT-Berufe); G 1.2.3 Qualifikationsentwicklungen; MINT-Berufe; Fachkräftemangel; Arbeitsmarktprognose; Qualifikationsentwicklung; Beruflicher Verbleib; Quantitative Angaben